A rare variation in the branching pattern of the axillary artery: a case report - Umanath, Preethi; Selvaraj, Sutha (Chulalongkorn Medical Journal, 2025)
This report presents a rare anatomical variation that was observed during the routine dissection of a male cadaver. The third part of the left axillary artery revealed a complete absence of the anterior and posterior circumflex humeral arteries. An unusual ascending branch originated from the arteria profunda brachii, a branch of the brachial artery. This aberrant branch divided further into a deltoid branch, which accompanied the axillary nerve through the quadrangular space to supply the deltoid muscle and terminated at the shoulder joint, and a nutrient branch, which supplied the head of the humerus. To the best of our knowledge, this variation has not been previously reported. Recognition of such vascular anomalies is important for surgeons, radiologists, and anatomists to prevent intraoperative complications and ensure the accurate interpretation of imaging.